1974
DOI: 10.5834/jdh.24.240
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effect of Chlorhexidine and the Development of Resistant Strains, of Bacteria

Abstract: The effect of mouthrinses and topical application of chlorhexidine on the development of dental plaque and gingivitis in man;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A problem which often arises in a prolonged application of antibiotics is the occurrence of resistant bacterial strains but it was established by ARITA et al, though in vitro [22], that the oral microbiota failed to develop any resistant strains. Throughout the scope of this study no particular resistant strains were observed to increase at any given stage and, from this, it was reasonably assumed that the resistant strains to chlorhexidine digluconate seldom occur in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…A problem which often arises in a prolonged application of antibiotics is the occurrence of resistant bacterial strains but it was established by ARITA et al, though in vitro [22], that the oral microbiota failed to develop any resistant strains. Throughout the scope of this study no particular resistant strains were observed to increase at any given stage and, from this, it was reasonably assumed that the resistant strains to chlorhexidine digluconate seldom occur in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%